Altered Behavior in Mice Socially Isolated During Adolescence Corresponds With Immature Dendritic Spine Morphology and Impaired Plasticity in the Prefrontal Cortex - Medendorp, William E.; Petersen, Eric D.; Pal, Akash; Wagner, Lina-Marie; Myers, Alexzander R.; Hochgeschwender, Ute; Jenrow, Kenneth A. (Frontiers in Behavioral Neuroscience, 2018)
Mice socially isolated during adolescence exhibit behaviors of anxiety, depression, and impaired social interaction. Although these behaviors are well documented, very little is known about the associated neurobiological changes that accompany these behaviors. It has been hypothesized that social isolation during adolescence alters the development of the prefrontal cortex, based on similar behavioral abnormalities observed in isolated mice and those with disruption of this structure. To establish relationships between behavior and underlying neurobiological changes in the prefrontal cortex, Thy-1-GFP mice were isolated from weaning until adulthood and compared to group-housed littermates regarding behavior, electrophysiological activity, and dendritic morphology. Results indicate an immaturity of dendritic spines in single housed animals, with dendritic spines appearing smaller and thinner. Single housed mice additionally show impaired plasticity through measures of long-term potentiation. Together these findings suggest an altered development and impairment of the prefrontal cortex of these animals underlying their behavioral characteristics.